Digital Learning Ecosystems and Their Role in Advancing Literacy and Conceptual Understanding in Physics - Lia Angraeni; Lukman Hakim Assegaf; Ira Novita Sari; Nurussaniah Nurussaniah; Khaerus Syahidi (Journal of Educational Studies, 2026)
Background of study: The rapid integration of digital technologies into education offers opportunities to address the persistent challenges of abstract physics learning, while the simultaneous development of digital literacy and conceptual understanding remains underexplored. Aims: This study aimed to investigate the impact of holistic digital learning on students’ digital literacy and conceptual understanding in physics, and to explore the relationship between these two constructs. Methods: A quasi-experimental non-equivalent control group design was applied with 67 senior high school students in Pontianak, Indonesia. The experimental group (n = 35) received instruction via a Moodle-based learning management system integrating blogs, digital worksheets, and interactive videos, while the control group (n = 32) engaged in conventional non-digital learning. Data were collected through pretest and posttest assessments based on Bloom’s taxonomy and the UNESCO digital literacy framework. Result: Welch’s ANOVA showed no significant pretest differences, but posttest results revealed significant gains in the experimental group for both digital literacy and conceptual understanding (p < .001). A strong positive correlation was also found between the two constructs (r = .843, p < .001). Implication: The findings demonstrate that holistic digital learning significantly enhances both digital competencies and conceptual mastery in physics, underscoring the importance of integrated digital ecosystems in meeting the dual demands of 21st-century education